The relationship between the applied torque and stresses in post-tension structures - Liew, Fui Kiew (Universiti Malaysia Sarawak, UNIMAS, 2007)
This research presents the non-destructive testing (NDT) method to determine the resultant stresses in mild steel bar usually employed in structures. The technique utilized ultrasonic pulse-echo that determined the wave velocity change due to torque applied between bolt and nut. Mild steel bar with nominal diameter of 18 mm and 25 mm were used. The specimen was loaded by means of a torque wrench, which gave the required amount of moment of about 240 Nm.